PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS IV SDN 028 SINTONG - Eli Hasmita; Makhdalena '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research is a classroom action research that aims to improve learning outcomes by implementing IPS cooperative learning model Example non example. The subjects were students of class VI SDN 028 Sintong in the second semester of the academic year 2015/2016, which amounted to 20 people with a level of academic ability heterogeneous. This study was conducted by two cycles and at the end of each cycle conducted daily tests. Data collected through observation and tests in the form of sheets daily tests. Results of research on the observation sheet shows the activity of teachers and students have done well after doing the action. Most students seemed excited and actively participate in the learning process is carried out, as in doing step by step learning, presenting worksheets or questions and respond to his presentation. Students are also trying to solve problems that teachers provide well. The action is said to be successful if the number of students who reach KKM increase in daily tests daily tests I and II. The number of students who reach KKM on a base score, daily test I (first cycle), daily test II (second cycle) respectively was 65.35%, 68.75% and 83.75%. Improving student learning outcomes from a base score to the first cycle increased by 34%, while the second cycle increased by 10%. The results of this study indicate that cooperative learning Example non example can improve student learning outcomes in social studies class VI SDN 028 Sintong in the second semester of the academic year 2015/2016.Keywords: Learning Outcomes IPS , Non Cooperative Learning Example Example , Classroom Action Research